Community art practices to elevate spiritual and environmental awareness - Abdi, Amir (fi=Lapin yliopisto|en=University of Lapland|, 2023)
The purpose of my research study is exploring possibilities of impacting spiritual and environmental awareness of art event participants by engaging them in community art projects.Structured participatory art research was conducted between dozens of participants and resulted in various art events and spiritual exercises, there are two artistic parts contributing to research data collection: the bio-art work made with community together with living fungi and second part is documentary film presenting the art creation process.The documentary “Community Based Art Project Chatra-BioMandala" can be watched online at https://youtu.be/t57iZ3_zRdw My qualitative analysis shows positive interest of participants and people interested in spiritual art topics on one hand and dispirited attitude from policy makers in the media field on the other hand.The main conclusions of my research are that participation in spiritual-environmental art events significantly promotes positive impact on the mental wellbeing of participants who are interested and in need of this type of support while seeming irrelevant to outsiders.